Etika Bisnis dalam Perspektif Islam - Abdul Ghafur (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2018)
In 1997-1998 Indonesia experienced a monetary crisis and economic crisis, where one of the factors causing it is the existence of economic wideenization. The image arises because the business ethics of entrepreneurs in Indonesia is low. If analyzed more deeply, the phenomenon is called the term "seller's market", which means the market is dominated by the seller, where the powerful seller is doing a lot of monopoly activities by ignoring the business ethics that becomes an important spirit in business activities.To build a healthy culture in business then it is necessary to use Islamic business ethics that there is a principle about the Barometer of Person and Person Ketaqwaan is a means for worship to Allah SWT. But to start Islamic business ethics must do several things: (1) Intention Ikhlas Expect Ridha Allah SWT. (2) Professional (3) Honest & Trustful (4) Promoting Ethics of a Muslim (5) Not Breaking Sharia Principles (6) And the last is Ukhuwah Islamiyah.